Social aspects of dementia in Central Africa (EDAC Survey) - (:unkn) unknown (My University, 2016)
IntroductionAccording to the World Health Organization, dementia poses a public health problem in sub-Saharan Africa because of the growing number of elderly. But the perception of this condition is poorly documented in low-income countries.ObjectivesTo Identify and analyze the perceptions of dementia in different population groups more or less concerned. MethodA Cross sectional study was conducted following a general population survey on dementia between October and December 2008 in Bangui and February-March 2009 in Brazzaville. Five groups of subjects were involved. The stigmatization of people with dementia was assessed using scale consisting of 15 questions. The Stat View 5.0 and SAS 9.1.3 software were used for data analysis.ResultsThe subjects of the groups interviewed were dominated by women with the exception of nursing staff. There was no equivalent to the biomedical concept of dementia in the local languages of the two countries in which the study was conducted. The problems of inability to work (73.3 to 82.7%) and reduction in family income (55.7 and 79.0%) were reported by subjects with mild cognitive impairment. The emotional impact was dominated by concerns about the progression of cognitive problems (52.5 to 76.8%), sadness and anxiety (50.8 to 79.4%).ConclusionIn urban zones in Central Africa, we find that perceptions of dementia include traditional and magical-religious aspects, even among health care workers who supposed best placed to provide tailored information.
Keywords: African Research